Fiscal Policy during the Caliph Abu Bakr ash-Siddiq - Trisna Dwi Nur Rodhiyah; Khusnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islam maintains economic stability and growth and improves economic welfare. Fiscal policy has been known since the time of Rasulullah and Khulafarasyidin. The purpose of this study is to determine the economic policy or fiscal policy implemented by Abu Bakar as Sidiq during his caliphate. This study uses qualitative research with a literature review approach. The fiscal policy implemented during the Caliphate of Abu Bakar was to emphasize the zakat instrument as state revenue which was then stored in the Baitul Mal, and then distributed to Muslims. The zakat collection policy implemented by Caliph Abu Bakar had a significant influence on the economic stability of Muslims. In addition to zakat, Abu Bakar also implemented economic policies, namely khums, jizyah, and kharaj.